Theory and method in higher education research. Vol. 7 - Huisman, Jeroen; Tight, Malcolm (Emerald Publishing Limited, 2021)
Higher education research is a developing field internationally, which is attracting more and more researchers from a great variety of disciplinary backgrounds within and beyond higher education institutions. As such, it is an arena within which a wide range of theories, methods and methodologies is being applied. This volume explores several topics including critical race theory; the use of communities of practice theory; participant ethnography; and decolonization using indigenous principles. Including contributors from Canada, Luxembourg, Portugal, Spain, South Africa, the UK and the USA, this volume presents international perspectives on the application and development of theory and methodology in researching higher education.
Keywords: Education, Higher -- Research.; Education, Higher -- Research -- Methodology.; Education -- Higher.; "Higher & further education, tertiary education".; elektronické knihy; electronic books